Observation of substrate diffusion and ligand binding in enzyme crystals using high-repetition- rate mix-and-inject serial crystallography. (2021) - Pandey, Suraj; Calvey, George; Katz, Andrea M.; Malla, Tek Narsingh; Koua, Faisal H. M.; Martin-Garcia, Jose M.; Poudyal, Ishwor; Yang, Jay-How; Vakili, Mohammad; Yefanov, Oleksandr; Zielinski, Kara A.; Bajt, Sasa; et al.
No abstract available